Usefulness of endoscopic ultrasound-guided fine-needle aspiration with a forward-viewing and curved linear-array echoendoscope for small gastrointestinal subepithelial lesions - Yamabe, Akane; Irisawa, Atsushi; Bhutani, Manoop S.; Shibukawa, Goro; Abe, Yoko; Saito, Akiko; Imbe, Koh; Hoshi, Koki; Igarashi, Ryo (Endoscopy International Open, 2015)
Background and study aims: It is difficult to perform endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) of small gastrointestinal (GI) subepithelial lesions (SELs) approximately 10 mm in diameter. This study was undertaken to evaluate the feasibility, safety, and diagnostic ability of EUS-FNA with a forward-viewing and curved linear-array echoendoscope (FVCLA-ES) that has a cap for small SELs.Patients and methods: The study enrolled 8 patients who had small upper GI SELs approximately 10 mm in diameter. To fix the SELs during FNA, a cap device was attached to the scope tip.Results: The mean (standard deviation [SD]) diameter of the SELs was 10.6 mm (2.94). Even small lesions were well targeted for FNA when the FVCLA-ES with a cap device was used. The mean (SD) number of passes was 4.6 (1.59). Adequate samples were obtained from 7 patients (87.5 %) – in 6 (75 %) for cytology and in 4 (50 %) for histologic examination with immunohistochemical (IHC) staining. No complication occurred. Gastrointestinal stromal tumor (GIST) in 2 patients and leiomyoma in 2 patients were definitively diagnosed with IHC staining.Conclusions: EUS-FNA with an FVCLA-ES that has a cap device is feasible and safe. This technique is expected to contribute to histologic diagnosis, even in small SELs.